The impact of computer-assisted personal interviewing on survey duration, quality, and cost: Evidence from the Viet Nam Labor Force Survey - Lakshman Nagraj Rao; Elisabetta Gentile; Dave Pipon; Jude David Roque; Vu Thi Thu Thuy (Global Labor Organization (GLO), 2020)
We use a randomized field experiment to estimate the effect of computer-assisted personal interviewing (CAPI) on interview duration, number of errors, respondent perceptions, and cost. During Quarter 3 of the 2017 Labor Force Survey data collection for Ho Chi Minh City, Viet Nam, 15 households were randomly selected and interviewed using pencil-and-paper interviewing (PAPI), while another 15 households were randomly selected and interviewed using CAPI within each of a total of 180 sample enumeration areas. On average, CAPI interviews lasted 9.4 minutes less and had 0.8 less errors per questionnaire relative to PAPI. Respondents were more likely to perceive interview duration as long or very long when the enumerator was female or educated to college level or above, which is contrary to our experimental findings. Finally, the break-even number of interviews that make CAPI cost-effective is 1,769, which is lower than prior estimates and reflects the rapidly decreasing cost of technology.
Keywords: C81; J21; 330; computer-assisted personal interviewing; data quality; randomized experiment; survey; labor statistics